Study on Wetted Soil Geometry of a Negative Pressure Irrigation (NPI) System. Issue 1 (1st May 2022) - Moniruzzaman, S. M.; Fukuhara, Teruyuki; Arifuzzaman, Md.; Rahman, Muhammad
Abstract: The limited water resource is a main constraint on agricultural production in arid and semi-arid regions like Saudi Arabia. The Negative Pressure Irrigation (NPI) is one of the attractive irrigation systems since it consumes less water, leads irrigated water down up to root zone, minimizes evaporation and prevents deep percolation than other traditional irrigation systems. The aim of this paper is to get information on the soil water dynamics, which is very essential for the design and operation of the NPI system. With this view, the water balance experiment was carried out in the NPI system for different time intervals for three different negative pressures ( Pn = -0.02m, -0.07m and -0.10m). After finishing the experiment, the dry soil was removed from the column to measure the configuration of wet soil. This geometry of wetted soil represents the soil water dynamics and the wetted soil volume represents the water stored in soil at different negative pressures and elapsed time. A good relationship was obtained between the wetted soil geometry, time and negative pressure. This study reveals that for a certain negative pressure and time interval, the depth, width and volume of wetted soil can be predicted.